Students' performances in solving 2nd Degree Equations with one Unknown - Aygor, Nilgun; Burhanzade, Hulya (ELSEVIER SCIENCE BV, 2015)
The purpose of this study is to examine the performance showed by the students in solving 2nd degree equations (quadratic equation) with one unknown. The study made use of qualitative research. Sample of the resarch is 23 10th grade students from two different schools, Anatolian Turgutlu High School and Milli Piyango Anatolian High School in Turgutlu district in the city of Manisa in the academic year 2012-2013. In order to collect the research data, 5 quadratic equations with one unknown whose degrees of difficulty are not the same were selected from the different textbooks relevant to the topic. The data obtained have been analyzed by the researchers. As a result of the research, it is determined that all of the students know the formulas as they memorize the required formulas while solving a quadratic equation with one unknown. Therefore, it is observed that the entire students solved the question in case of the question type in which the formula is directly applied. It is found that even though a portion of students knows the formulas they did not know how to solve the question by putting information together. In other words, it is observed that for the question types which can be solved by making interpretation the students made mistakes and even the vast majority of them could not solve the question. The students also need the information of square root concept so as to be able to solve the questions. Some questions containing square root concept in solving quadratic equation with one unknown were found difficult by the students. (C) 2015 Published by Elsevier Ltd.
Keywords: Mathematics education; 2nd degree equations with one unknown (quadratic equation with one unknown); the achievement of solving equation; Education & Educational Research; Social Sciences - Other Topics